Challenges and Opportunities in E-Commerce Development in Nepal - Sharma, Deepak (Journal of Nepal Commerce Association, 2025)
This research paper investigates the challenges and opportunities associated with the development of e-commerce in Nepal. The purpose of the study is to provide a comprehensive analysis of the factors that influence e-commerce growth, focusing on both obstacles and potential avenues for expansion. The study employs a secondary data methodology, drawing from existing literature, industry reports, and relevant case studies to present a nuanced view of the e-commerce landscape in Nepal. Key findings reveal that while e-commerce in Nepal faces significant challenges such as inadequate infrastructure, regulatory hurdles, and limited digital literacy, there are substantial opportunities fuelled by increasing internet and smartphone penetration, a growing middle class, and supportive government policies. The practical implications of this study are relevant for policymakers, business leaders, and investors, offering strategic insights into overcoming the identified challenges and capitalizing on growth opportunities. The originality and value of this paper lie in its focused examination of Nepal's e-commerce sector, providing a foundation for future research and policy formulation aimed at fostering a robust digital economy.